Optimization of Foaming Condition and Drying Behavior of White Button Mushroom (Agaricus bisporus). Issue 6 (19th August 2014) - Pasban, Atena; Mohebbi, Mohebbat; Pourazarang, Hashem; Varidi, Mehdi; Abbasi, Arezoo
Abstract: Foaming conditions of button mushroom ( A garicus bisporus ) puree were optimized using response surface methodology with respect to cress seed gum concentration (0.3–0.6% w/w), mushroom puree to water ratio (1:0.5–1:2.5 w/w) and whipping time (2–8 min) for minimum foam density and foam drainage volume as response variables. Finally, optimized foam was dried at 50, 65 and 80C to an equilibrium moisture content using a hot air dryer, and values of effective diffusivities and activation energy were determined. The optimized conditions were found at cress seed gum concentration = 0.57% w/w, mushroom puree to water ratio = 1:0.5 and whipping time = 6.49 min. The predicted values of foam density and foam drainage volume were 0.58 g/cm 3 and 2.9 mL, respectively. The effective moisture diffusivity of mushroom foam mats ranged from 4.765 to 10.42 × 10 –9  m 2 /s. Practical Applications: The white button mushroom is the most popular edible mushrooms with short shelf life. One approach intended to increase consumption of mushroom is to produce mushroom powder for using as an ingredient into instant soup, snacks, baby foods and other products. Foam mat drying is a novel, improved and economical method for drying liquid or semiliquid foods to obtain products with desired properties. Preparation of the stable foam plays major role in foam mat drying. In this context, foaming condition of white mushroom was optimized and drying behavior was studied.